2012
DOI: 10.1590/s0104-66322012000300010
|View full text |Cite
|
Sign up to set email alerts
|

Organophilic bentonites based on argentinean and Brazilian bentonites: Part 1: influence of intrinsic properties of sodium bentonites on the final properties of organophilic bentonites prepared by solid-liquid and semisolid reactions

Abstract: -This study describes the influence of the intrinsic properties of raw materials on the organophilization of bentonites from Argentinean raw sodium bentonites and Brazilian sodium activated bentonites. The organophilization was done with two methodologies: solid-liquid and semisolid reactions. Correlations between the properties of sodium and organophilic bentonites were established. The effectiveness of the treatments was verified by X-ray diffraction, swelling capacity in water and xylene and SEM to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
2
15
0
1
Order By: Relevance
“…This hypothesis is more convincing and explains better the fact that some of the samples showed the same structure of the organophilic clay. Besides, it is the more probable hypothesis for the occurrence of the three diffraction peaks discussed previously in Part 1 of this work (Paiva and Morales, 2012). Zhang et al (2005) also observed the presence of three diffraction peaks in the X-ray patterns of organophilic clays and nanocomposites of polyethylene and PP, where the original structure of the organophilic clay was preserved.…”
Section: Evaluation Of the Nanocomposite Structures By X-ray Diffractionsupporting
confidence: 74%
See 1 more Smart Citation
“…This hypothesis is more convincing and explains better the fact that some of the samples showed the same structure of the organophilic clay. Besides, it is the more probable hypothesis for the occurrence of the three diffraction peaks discussed previously in Part 1 of this work (Paiva and Morales, 2012). Zhang et al (2005) also observed the presence of three diffraction peaks in the X-ray patterns of organophilic clays and nanocomposites of polyethylene and PP, where the original structure of the organophilic clay was preserved.…”
Section: Evaluation Of the Nanocomposite Structures By X-ray Diffractionsupporting
confidence: 74%
“…In our previous work (Paiva and Morales, 2012) the intrinsic properties of sodium bentonites were evaluated and correlated with their organophilization capacity. This work evaluates composites produced from these organophilic bentonites, which were modified by two different methodologies: in aqueous dispersion and semisolid medium.…”
Section: Introductionmentioning
confidence: 99%
“…This occurrence of a peak before 2θ = 10 Å is representative of the basal spacing, d 001 , of the smectite clay (Moore and Reynolds, 1997). The low value of 2θ respect to the plane 001 and, thus, a high value of basal spacing when compared with no organophilic clays, are related to the salt which was inserted in the organophilization process of the clay, which promotes the advance angle 2θ due to the changes caused in the clay structure (Paiva and Morales, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…These organoclays are clays modified by insertion of organic molecules to increase the compatibility between the clay and the organic medium. These organic molecules are interspersed among the structural layers and cause expansion between the planes of the clay, and change their hydrophilic nature to hydrophobic and/or organophilic …”
Section: Introductionmentioning
confidence: 99%
“…These organic molecules are interspersed among the structural layers and cause expansion between the planes of the clay, and change their hydrophilic nature to hydrophobic and/or organophilic. [14] Thus, new techniques for treating these effluents are emerging, including the adsorption of contaminants in organoclays. [9,15] Therefore, the aim of this study is to evaluate the potential of the commercial organoclay Spectrogel 1 for the treatment of wastewater contaminated with toluene.…”
Section: Introductionmentioning
confidence: 99%